Key issues in education and social justice - Smith, Emma (Education studies, key issues., 2018)
"This book is an introduction to issues of inequality and social justice, how they relate to education systems and how education can be a force for positive societal change. Drawing upon research, policy and contemporary thinking in the field, this second edition examines educational inequalities that exist today, what lies behind them and what effects they have across society."--Provided by publisher.